Recent application developments of water-soluble synthetic polymers - Halake, Kantappa; Birajdar, Mallinath; Kim, Byoung Soo; Bae, Harim; Lee, CheongCheon; Kim, Yoo Jin; Kim, Sinwoo; Kim, Hyun Jin; Ahn, Soohwan; An, Su Yeoung; Lee, Jonghwi (Journal of industrial and engineering chemistry (Seoul, Korea), 2014)
This paper explores recent findings in water-soluble hydrophilic polymers application research, and will guide the general audience in the area of applied chemistry toward intriguing issues. In the history of man-made macromolecules, water-soluble polymers have primarily maintained passive roles; examples include the uses of water-soluble polymers for viscosity control and as binders. The importance of water on earth has increased research into the development of active roles for water-soluble polymers. These expanding roles span from medical applications, such as drug delivery to environmental applications, such as the removal of heavy metals. The development of water-soluble polymers brings significant benefits to the structural engineering and production of nanomaterials and electronic materials. The current limits of the structure–property relationship have been challenged to meet these rapidly-developing application areas.